Sequential dissection of multiple ionic currents in single cardiac myocytes under action potential-clamp - Banyasz, Tamas (2011)
The cardiac action potential (AP) is shaped by myriad ionic currents. In this study we develop an innovative AP-clamp Sequential Dissection technique to enable recording of multiple ionic currents in the single cell under AP-clamp. This new technique presents a significant step beyond the traditional way of recording only one current in any one cell. The ability to measure many currents in a single cell has revealed two hitherto unknown characteristics of the ionic currents in cardiac cells: coordination of currents within a cell and large variation of currents between cells. Hence, the AP-clamp Sequential Dissection method provides a unique and powerful tool for studying individual cell electrophysiology.